The relations between China and the countries of South Europe: The case of Portugal - Costa, C. M.; Costa, C M; Freire, A. (2020)
Cátia Miriam Costa & André Freire (2019), « The relations between China and the countries of South Europe: The case of Portugal», Report for the Friedrich Ebert Foundation Cyprus in a set of 5 Reports (from Cyprus, Greece, Italy, Portugal, and Spain) about the relations of South European Countries and China in current times, coordinated by Yiannos Katsourides, non-published report.